Design, Fabrication and Evaluation of Drug Release Kinetics from Aceclofenac Matrix Tablets using Hydroxypropyl Methyl Cellulose - Kabir, Abul Kalam Lutful; Biswas, Bishyajit Kumar; Rouf, Abu Shara Shasur (Dhaka University Journal of Pharmaceutical Sciences, 2010)
The objective of this study was to develop a sustained release matrix tablet of aceclofenac using hydroxypropyl methylcellulose (HPMC K15M and HPMC K100M CR) in various proportions as release controlling factor by direct compression method. The powders for tableting were evaluated for angle of repose, loose bulk density, tapped bulk density, compressibility index, total porosity and drug content etc. The tablets were subjected to thickness, weight variation test, drug content, hardness, friability and in vitro release studies. The in vitro dissolution study was carried out for 24 hours using United States Pharmacopoeia (USP) 22 paddle-type dissolution apparatus in phosphate buffer (pH 7.4). The granules showed satisfactory flow properties, compressibility index and drug content etc. All the tablets complied with pharmacopoeial specifications. The results of dissolution studies indicated that the formulations F-2 and F-3 could extend the drug release up to 24 hours. By comparing the dissolution profiles with the marketed product, it revealed that the formulations exhibited similar drug release profile. From this study, a decrease in release kinetics of the drug was observed when the polymer concentration was increased. Kinetic modeling of in vitro dissolution profiles revealed the drug release mechanism ranges from diffusion controlled or Fickian transport to anomalous type or non-Fickian transport, which was only dependent on the type and amount of polymer used. The drug release followed both diffusion and erosion mechanism in all cases. The drug release from these formulations was satisfactory after 3 months storage in 40°C and 75% RH. Besides, this study explored the optimum concentration and effect of polymer(s) on acelofenac release pattern from the tablet matrix for 24 hour period. Key words: Aceclofenac; sustained release; hydrophillic matrix; HPMC; direct compression. DOI: 10.3329/dujps.v8i1.5332 Dhaka Univ. J. Pharm. Sci. 8(1): 23-30, 2009 (June)